Tingkat Literasi Media Remaja Desa dalam Pemanfaatan Internet - Rully Novianti; Sutisna Riyanto (Jurnal Komunikasi Pembangunan, 2018)
The development of Information and Communication Technology (ICT) is increasing rapidly, causing the internet utilization patterns become more varied, both for positive purposes and negative purposes. In order to avoid the negative effects of the internet, media literacy is required for internet users. The purpose of this research is to analyze the influence of respondent's characteristic to the media literacy level of young villager and to analyze the correlation between media literacy level of young villager and the utilization of internet by using 45 members of Cibanteng Village’s youth organization as respondents. This research is conducted by using quantitative approach supported by qualitative data. The results of this study indicate that there are respondent’s characteristics that significantly influence media literacy’s level of young villager and media literacy’s level of young villager significantly related with internet utilization.